Impact of land use land cover changes on urban temperature in Jakarta: insights from an urban boundary layer climate model - Maheng, Dikman; Pathirana, Assela; Bhattacharya, Biswa; Zevenbergen, Chris; Lauwaet, Dirk; Siswanto, Siswanto; Suwondo, Aries (Frontiers in Environmental Science, 2024)
Urbanization is one of the important drivers of increasing local temperatures. As cities and urban areas evolve, extensive land use and land cover (LULC) changes alter the physical characteristics of surface materials. This modification results in reduced evapotranspiration rates, ultimately contributing to higher surface and air temperatures. This study investigated the impact Maheng et al.provides an alternative approach to many existing methods that provide general information about temperature changes, without specifically analyzing the effects of LULC transformations.